Jual Beli Hak Atas Tanah Berdasarkan Akta Kuasa Menjual Notariil - Dwi Hartiningsih (Lex Renaissance, 2020)
This research examines the sale and purchase of land rights based on the notarial power of attorney to sell in Magelang Regency. The problems formulated are first, what has been the consideration of the Magelang Regency National Land Agency (BPN) to limit the validity of the notarial deed stating capacity to selling; and second, how is the settlement made by PPAT in relation to the sale and purchase of land based on the notarial power of attorney to sell which is limited by BPN. This is a normative-empiric research supported by information obtained from the respondents and analysed using statutory and conceptual approach with qualitative descriptive method. Hence in this study, primary and secondary legal materials were used. This research concludes that first, BPN's consideration in limiting the validity period of the power of attorney to sell power deed has no legal basis but only based on the precautionary principle, in implementing this principle, however, BPN has not carried out any socialization steps to the public in general and notaries in particular, so that future similar problems may be solved quickly and accurately and does not deviate from the existing norms and/or regulations. Second, the steps taken by PPAT in resolving this issue include approaching and reviewing regulations while finding the best and most effective solution in resolving problems with the BPN of Magelang Regency.